2022
DOI: 10.3389/fpls.2022.898256
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Regulatory Pattern Analysis of Soybean Ca2+ ATPases for Abiotic Stress Tolerance

Abstract: P2-type Ca2+ ATPases are responsible for cellular Ca2+ transport, which plays an important role in plant development and tolerance to biotic and abiotic stresses. However, the role of P2-type Ca2+ ATPases in stress response and stomatal regulation is still elusive in soybean. In this study, a total of 12 P2-type Ca2+ ATPases genes (GmACAs and GmECAs) were identified from the genome of Glycine max. We analyzed the evolutionary relationship, conserved motif, functional domain, gene structure and location, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…79 Previous studies have shown that when plants were severely stressed, Ca 2+ pumps (ACA) located on the plasma membrane and tonoplast are preferentially mobilized in a unified manner, which can rapidly generate Ca 2+ oscillation to regulate plant response to external stresses. 80 Our study showed that the expression of calciumtransporting ATPase (GsACA11 and A0A0B2Q562) was obviously induced under saline−alkaline stress. The overexpression of GsACA11 in yeast cells and the composites of soybean proved that it could confer saline−alkaline stress tolerance (Figures 7 and 8).…”
Section: Saline−alkaline Stress Inducesmentioning
confidence: 61%
See 1 more Smart Citation
“…79 Previous studies have shown that when plants were severely stressed, Ca 2+ pumps (ACA) located on the plasma membrane and tonoplast are preferentially mobilized in a unified manner, which can rapidly generate Ca 2+ oscillation to regulate plant response to external stresses. 80 Our study showed that the expression of calciumtransporting ATPase (GsACA11 and A0A0B2Q562) was obviously induced under saline−alkaline stress. The overexpression of GsACA11 in yeast cells and the composites of soybean proved that it could confer saline−alkaline stress tolerance (Figures 7 and 8).…”
Section: Saline−alkaline Stress Inducesmentioning
confidence: 61%
“…To maintain the intracellular ion homeostasis and prevent cellular injury, the plants efficiently export Ca 2+ into organelles or outside the cell . Previous studies have shown that when plants were severely stressed, Ca 2+ pumps (ACA) located on the plasma membrane and tonoplast are preferentially mobilized in a unified manner, which can rapidly generate Ca 2+ oscillation to regulate plant response to external stresses . Our study showed that the expression of calcium-transporting ATPase (GsACA11 and A0A0B2Q562) was obviously induced under saline–alkaline stress.…”
Section: Discussionmentioning
confidence: 99%
“…We further tested the method in the Glycine max assembly, where P2 family ATPases have already been annotated [ 33 ]. The G. max genome assembly used here has a scaffold N50 of 48 Mb and a contig N50 of 419 kb.…”
Section: Resultsmentioning
confidence: 99%
“…An HMM has been used to identify soybean P2-type Ca 2+ ATPase genes in the G. max genome [32]. Using the automatic annotation according to these criteria, 12 P2-type ATPases were identi ed, which is a number far below the 23 P2A/B ATPases we identi ed in this genome using our method based on the expanded two motifs.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%